Analisis Efektivitas Biaya Penggunaan Antibiotik terhadap Pasien Sepsis di RSD dr. Soebandi TahunAnalisis Efektivitas Biaya Penggunaan 2014-2015 (Cost Effectiveness Analysis of Antibiotic Used for Sepsis Patients in dr. Soebandi Hospital During 2014-2015) - Putri Kartika Ningsih; Prihwanto Budi Subagijo (Pustaka Kesehatan, 2017)
Sepsis is a medical condition that is difficult to be identified and diagnosed. Sepsis often occurs to hospitalized patients in the hospital. Treatment with antibiotics is one of the factors supporting the success of sepsis treatment. The purpose of this study was to determine the most effective empirical antibiotics based on the cost effectiveness of adult and geriatric sepsis patients in RSD dr. Soebandi Jember during 2014-2015. This observational study was conducted by retrospective data collection. Data was collected from hospitalized sepsis patients medical records and received empirical antibiotics therapy at least three days. The parameters used in this study were costs which included the cost of accommodation, examination support, services, medicines, and medical devices, while the effectiveness used the length of stay, length of antibiotic related and the patients life expectancy. The results of incremental cost effectiveness ratio (ICER) showed that meropenem antibiotic had a lower cost Rp 378,808.07 compared to ceftazidime and cefotaxime. It can be concluded that meropenem antibiotic was more cost effective than ceftazidime and cefotaxime antibiotics. Keywords: cost effectiveness, pharmacoeconomic, antibiotic, sepsis